PELAKSANAAN PEMENUHAN PELAYANAN KESEHATAN BAGI NARAPIDANA DI LEMBAGA PEMASYARAKATAN NARKOTIKA (STUDI PADA LEMBAGA PEMASYARAKATAN NARKOTIKA KELAS IIA JAKARTA PERIODE 1 JANUARI 2023 S/D 31 DESEMBER 2023) - Aditya Putra, Firman; Lumban Gaol, Selamat (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
Fulfillment of health services for prisoners is very important in the treatment and rehabilitation of prisoners who are involved in narcotics abuse. The role of the Lapas Narkotika Kelas IIA Jakarta, especially in health services for convicts, therefore has a special responsibility to provide health services in addition to treatment for those who have been caught up in narcotics abuse. This research will discuss the Regulation of Health Services for Prisoners in Narcotics Prisons and Obstacles in Implementing Health Services for Prisoners in Lapas Narkotika Kelas IIA Jakarta for the Period 1 January to 31 December 2023. The legal research method used is a normative juridical legal research method supported by data empirical. Using a legal approach obtained from primary, secondary and tertiary legal material sources. Regulations on Health Services for Prisoners in Narcotics Prisons Article 28 H paragraph (1) of the 1945 Constitution of the Republic of Indonesia, then Regulations on the Right to Health Services in Article 62 of Law 39/1999, then Service Regulations also contained in Articles 30 to 32, 65 to 73, and 86 to 95 of Law 17/2023. Health Services and Regulations for Inmate Health Services in Narcotics Prisons are the same as in prisons in general, regulated in Article 9 letter (d) of Law 22/2022. Obstacles in the Implementation of Fulfillment of Health Services for Prisoners in Lapas Narkotika Kelas IIA Jakarta for the Period 1 January to 31 December 2023, namely the Number of Prison Inmates that exceed Capacity, Limited Health Personnel in Correctional Institutions, Lack of Facilities and Infrastructure, Awareness and Concern of Prisoners with Poor Health and Discrimination of Prisoners in Hospitals When Referrals are Made.